Pengaruh Komisaris Independen, Leverage, Dan Kepemilikan Institusional Terhadap Integritas Laporan Keuangan - Novianti, Sinta; Isynuwardhana, Deannes (Universitas Pendidikan Indonesia, 2021)
Several cases that occurred in several companies in Indonesia, such as manipulation of financial statements, showed that the integrity of the financial statements presented by the company was still low. To avoid manipulation, it requires concervative accounting practices. This study aims to determine how the influence of independent commissioner variables, leverage, and institutional ownership on the financial statements integrity. This study’s population are all mining sector companies listed on the Indonesia Stock Exchange in 2015-2018. The samples produced were 128 samples using purposive sampling. Data in this study were analyzed with descriptive statistical analysis and panel data regression using Software Eviews 9.0. This study indicates that independent commissioners, leverage, and institutional ownership simultaneously influence the integrity of financial statements. Partially, leverage has a significant positive effect on the integrity of financial statements. In contrast independent commissioners and institutional ownership have no significant effect on the integrity of financial statements